Evaluation of Accounting Information System in The Cycles of Purchases And Sales of Merchandise at Amanah Store - Imanniah Sukmarini; Yuliati Yuliati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
Amanah Store is an agent for selling packaged snacks and beverages wholesale and retail. Amanah Store does not produce its goods but only resells, so it is categorized as a trading company. This research aims to evaluate related to the cycle of purchasing and selling merchandise at Amanah Stores based on several problems found. As a sales agent for packaged snacks and beverages, the operational activities are very high. However, the owned organizational structure is not optimal because there is no specific division of tasks. This affects the cycle of purchasing and selling cycles because there are no particular essential parts. The method used in this research is a qualitative research method using a case study approach. The data used are primary data obtained directly from the research location. The data collection techniques used were interviews, observation, and documentation. Interviews were conducted directly at the research location with the selected subjects as informants. Informants were selected using a purposive sampling technique, where the person was chosen because he or she was considered the most knowledgeable about the company. Observations are carried out directly by observing the activities that occur in the company, and documentation is carried out to strengthen the research data. To obtain valid data, validity was also carried out, whereas, in this study, the validity was carried out using triangulation methods, namely testing data from interviews, observations and documentation. The results of this study are that the accounting information system cannot be said to be optimal if the functions needed in the organizational structure have not explicitly been divided. Besides that, transaction documents and accounting records are also incomplete because no function or section is specifically responsible for handling